Mathematical Modelling of Malaria with Treatment (Advances in Applied Mathematics and Mechanics, 2021)
This paper proposes a Susceptible-Infective-Susceptible (SIS)model to study the malaria transmission with treatment by considering logisticgrowth of mosquito population. In this work, it is assumed that the treatmentrate is proportional to the number of infectives below the capacity and isconstant when the number of infectives is greater than the capacity. We findthat the system exhibits backward bifurcation if the capacity is small and itgives bi-stable equilibria which makes the system more sensitive to the initialconditions. The existence and stability of the equilibria of the model arediscussed in detail and numerical simulations are presented to illustrate the numerical results.